Produção In Vitro de embriões bovinos - Silva, Gisele Ramos da (Universidade Federal do Tocantins, 2023)
The mandatory supervised internship, which as the last discipline of the Veterinary Medicine Course at the Universidade Federal do Norte do Tocantins (UFNT) aims to experience the professional practice. It was carried out at the Universidade Federal do Pará (UFPA) campus Castanhal, adding up to a total of 408 hours of internship in the period from March 13 to May 24, 2023. Supervised by Prof. Dr. Francisca Elda Ferreira Dias and supervised by Prof. Dr. Adriana Novaes dos Reis. The activities developed were performed in two sectors, the Central Animal Reproduction Biotechnology Center (CEBRAN), where activities of reproductive management and clinic of large animals were developed, and the Laboratory of Biotechnology and Medicine of Animals of the Amazon (BIOMEDAM), where laboratory practices were concentrated, with emphasis on the in vitro production of embryos (IVPE) and laparoscopic ovum pick up (LOPU). This report describes the routine in more detail during this period, focusing on IVPE.